2000
DOI: 10.1161/01.cir.101.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of Local Angiotensin II Activity Mediated via Type 1 Receptor in the Pathogenesis of Cardiovascular Inflammatory Changes Induced by Chronic Blockade of Nitric Oxide Synthesis in Rats

Abstract: Increased Ang II activity mediated via the type 1 receptor may thus be important in the pathogenesis of early cardiovascular inflammatory changes in this model. Endothelium-derived NO may decrease MCP-1 production and oxidative stress-sensitive signals by suppressing localized activity of Ang II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
115
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 35 publications
15
115
0
1
Order By: Relevance
“…In general, oxidative stress is considered to participate to the development of vascular inflammation (53,54). Previous studies (48, 54−56) have suggested that L-NAME treatment enhances oxidative stress in the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…In general, oxidative stress is considered to participate to the development of vascular inflammation (53,54). Previous studies (48, 54−56) have suggested that L-NAME treatment enhances oxidative stress in the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…This dose of olmesartan has no effect on AngII-induced increase in arterial pressure. 26 The fifth group (shamϩ7ND group, nϭ10) received physiological saline and intramuscular injections of pcDNA3-7ND plasmid DNA (100 g).…”
Section: Treatmentmentioning
confidence: 99%
“…This dose of olmesartan has no effect on AngII-induced increase in arterial pressure. 26 The fifth group (shamϩ7ND group, nϭ10) received physiological saline and intramuscular injections of pcDNA3-7ND plasmid DNA (100 g).In the shamϩ7ND, AngIIϩplasmid, and AngIIϩ7ND groups, transgene expression was enhanced by local intramuscular electroporation at the injection site immediately after the injection. Six 100-V, 50-ms electronic pulses were applied to each injection site using an Electroporator CUY21 (BTX).…”
mentioning
confidence: 99%
“…7 Treatment with ARBs leads to a decrease in inflammation and adhesion molecules, such as CRP, 8 intercellular adhesion molecule-1, chemokines, E-selectin and monocyte chemotactic protein (MCP)-1. 9,10 In addition, monocyte and endothelial cell activation markers were significantly decreased in patients with type 2 diabetes after treatment with valsartan. 11 In addition, valsartan has been shown to be effective at preventing coronary restenosis in an open-label clinical study (Val-PREST).…”
Section: Introductionmentioning
confidence: 99%